Reception of the New Framework for Implementing Temporal Big Data Analytics in Organizations - Mach-Król, Maria (Recepcja nowych ram dla wdrożenia temporalnej analityki big data w organizacjach, 2022)
The main goal of this study was to present the reception of the new framework for implementing temporal big data analytics (TBDA) in organizations. This research also aimed at verifying the correctness and usefulness of the proposed framework by means of a focus group interview. The need for TBDA is described, and the proposed framework briefly outlined. Finally, the results of the focus group interview are presented. The proposed conceptual framework was positively verified. The most important findings of this study are: proving that effective implementation of big data analytics in companies requires consideration of time; demonstrating the usefulness of the leagile approach in the implementation of TBDA in companies; positive verification of the comprehensive conceptual framework for TBDA implementation in organizations.
Informatyka Ekonomiczna = Business Informatics, 2022, Nr 2 (64), s. 28-48
Keywords: temporal big data; implementation framework; temporal big data analytics; leagile approach; temporalne Big Data; ramy implementacji; temporalna analiza gig data; podejście leagile